2021
DOI: 10.1159/000515422
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAs and Their Therapeutic Promise in Diabetic Nephropathy

Abstract: Recent advances in large-scale RNA sequencing and genome-wide profiling projects have unraveled a heterogeneous group of RNAs, collectively known as long noncoding RNAs (lncRNAs), which play central roles in many diverse biological processes. Importantly, an association between aberrant expression of lncRNAs and diverse human pathologies has been reported, including in a variety of kidney diseases. These observations have raised the possibility that lncRNAs may represent unexploited potential therapeutic targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 104 publications
1
11
0
Order By: Relevance
“…More and more studies have demonstrated that lncRNA exerts a crucial role in various kinds of physiopathological processes such as genomic imprinting, gene expression, cell proliferation, tumorigenesis (de Oliveira et al, 2019, Bach and Lee, 2018, Sakatani et al, 2005). As expected, lncRNAs are abnormally expressed in DN patients and mice and exert an important role in the progression of DN (Coellar et al, 2021). The data from RNA sequencing show that 106 lncRNAs are dys-regulated in kidney tissues of DN mice and 42 lncRNAs are correlated with DN (Li et al, 2018).…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…More and more studies have demonstrated that lncRNA exerts a crucial role in various kinds of physiopathological processes such as genomic imprinting, gene expression, cell proliferation, tumorigenesis (de Oliveira et al, 2019, Bach and Lee, 2018, Sakatani et al, 2005). As expected, lncRNAs are abnormally expressed in DN patients and mice and exert an important role in the progression of DN (Coellar et al, 2021). The data from RNA sequencing show that 106 lncRNAs are dys-regulated in kidney tissues of DN mice and 42 lncRNAs are correlated with DN (Li et al, 2018).…”
Section: Introductionsupporting
confidence: 66%
“…MC injury, including hyperplasia, ECM production, and hypertrophy, plays a crucial role in the pathology of DN (Dai et al, 2017). LncRNA was reported to be involved in MC injury and DN progression (Coellar et al, 2021). However, the role of lncRNA in these processes is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…GAS5-lncRNA is a snoRNA host gene which encodes a large number of snoRNAs. In addition, a number of studies have linked this lncRNA to kidney function (42)(43)(44). Interestingly, this lncRNA is also a binding partner for SNORD118 described above (45).…”
Section: Members Of Other Srna Classesmentioning
confidence: 99%
“…Available evidence has indicated the important roles of lncRNAs in the pathophysiology of diabetic kidney disease (DKD), and the crosstalk between lncRNAs and DKD were reported in recent years [15][16][17][18][19]. Altered expression levels of lncRNAs play key roles in the development of proteinuria and associated diabetic nephropathy (DN) [15,20].…”
Section: Lncs In Diabetic Kidney Diseasementioning
confidence: 99%